Comprehensive performance of composite phase change materials based on ternary eutectic chloride with CuO nanoparticles for thermal energy storage systems. (15th January 2023) - Wang, Qing; Wu, Chunlei; Sun, Shipeng; Wang, Xinmin; Wu, Shuang; Cui, Da; Pan, Shuo; Sheng, Hongyu
Highlights: The proportion of ternary molten salt (NaCl-KCl-LiCl) was determined by simulation combined with experimental methods. Phase change material (NaCl-KCl-LiCl) and composite phase change materials (NaCl-KCl-LiCl/CuO) were prepared by mechanical stirring and static melting. CuO nanoparticles and ternary chlorine salt (NaCl-KCl-LiCl) form microscopic nanostructures. CuO nanoparticles improve their specific heat and thermal conductivity without changing the latent heat of ternary chlorine salt (NaCl-KCl-LiCl). Abstract: Herein, a novel phase change energy storage material based on a NaCl (15 wt%)-KCl (45 wt%)-LiCl (40 wt%) ternary molten salt and CuO nanoparticles with varying mass fraction as a heat transfer enhancer is produced through a combination of static melting and mechanical stirring methods. According to the microcosmic characterization data, a microphysical structure of a ternary chlorine salt, partially doped with CuO, is formed. According to the thermal analysis results, CuO nanoparticles are able to effectively improve specific heat, thermal conductivity and energy storage density of ternary chloride salts without any change in their melting point, freezing point and latent heat of fusion. In particular, the CuO nanoparticles with a 3% mass fraction are shown to be more appropriate as the enhanced heat transfer agents. The phase change materials produced in this study exhibit high heat transfer efficiency, high energy storage density and excellent high temperature cycling stability, which make them applicable in thermal energy storage systems.